2021
DOI: 10.16966/2378-7090.368
|View full text |Cite
|
Sign up to set email alerts
|

Dental Sedation: The Advantages of Propofol and Remifentanil via Target Controlled Infusions

Abstract: We prospectively audited 150 patients undergoing dental procedures with Target Controlled Infusion (TCI) of propofol and remifentanil to evaluate patient safety, adverse effects and post-operative discharge time and patient feedback. This anaesthetic technique provides for early recovery after surgery and allows for a 92% rate of “fast track” discharge within 20 minutes (mins) of completion of surgery. The technique proved safe with 14 patients (9.3%) experiencing a total of 14 adverse events, none of which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In this study, the remifentanil group had an average discharge time of 20.00±7,246 minutes. This is in accordance with a previous study of dental surgery patients receiving propofol and remifentanil, which showed a discharge time of about 20 minutes after surgery (DG et al, 2021). The results of this study are also in line with previous studies on short urological surgery, which stated that patients receiving remifentanil had lower Aldrete scores better than fentanyl with less sedative effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, the remifentanil group had an average discharge time of 20.00±7,246 minutes. This is in accordance with a previous study of dental surgery patients receiving propofol and remifentanil, which showed a discharge time of about 20 minutes after surgery (DG et al, 2021). The results of this study are also in line with previous studies on short urological surgery, which stated that patients receiving remifentanil had lower Aldrete scores better than fentanyl with less sedative effects.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical effect wears off in 2 to 5 minutes. Therefore, Remifentanil can provide controlled levels of sedation and analgesia with minimal or unsustainable side effects (DG et al, 2021;Pavlin et al, 1998). This study aims to compare the administration of fentanyl and remifentanil to the recovery time and discharge time of postodontectomy patients with general anesthesia.…”
Section: Introductionmentioning
confidence: 99%